Програмний модуль аналізу дозоформуючих параметрів рентгенівських діагностичних комплексів - Костіна, А. В.; Бих, А. І.; Печерська, А. І. (ХНУРЕ, 2018)
The actual scientifical task is the search for methods and technologies for reducing the dose of X-ray radiation, which the patient receives during diagnostic activities. One of the first tasks in this case is the tight control of the dose-forming parameters of X-ray diagnostic systems, which is advisable to solve with the use of modern information technologies. A software tool that consists of five interconnected modules that provide recording, processing, analyzing, storing information and generating a report on such dose-forming parameters as: resolution, threshold contrast, dynamic range, stability, voltage, power with closed blinds, radiation output, has been developed
Keywords: рентгенологічний метод; комп'ютерна обробка зображення; опромінення; дозоформуючі параметри